The Role of Peer to Peer Lending in Improving the Welfare of Village Community MSMEs - Yovita, Yovita; Rumbiati, Rumbiati; Syahid, Mar; Adiwijaya, Saputra; Utami, Eva Yuniarti (Journal Of Human And Education (JAHE), 2024)
Tegal Maja Village is one of the villages in Kragilan District, Serang Regency, Banten. Geographically, Tegal Maja Village is located in the middle and is very strategic. When discussing with members of the MSME Group in Tegal Maja Village, Kragilan District, Serang Regency, Banten, they had a number of problems as well as reasons why the Bamboo Craft business was not growing rapidly and even continued to decline every year. The problem in question is the lack of capital costs. To overcome this problem, an alternative solution that can be implemented is for the author to discuss with village officials who suggest collaborating with Fintech using the peer to peer lending method which is expected to be useful for improving the home business of the Tegal Maja Village Bamboo Craftsmen MSME group so that they are able to compete with competitors online. or offline. Therefore, the aim of this community service is to see the potential of using the role of Peer to Peer Lending in improving the welfare of the MSME community in Tegal Maja Village, Kragilan District, Serang Regency, Banten. To obtain the data used were observation and literature review. This service activity is an educational effort on the role of peer to peer lending in improving the welfare of the MSME community in Tegal Maja Village, Kragilan District, Serang Regency, Banten. As a form of thought, the author offers several efforts and breakthroughs, namely: 1.) Provide education on how to use Fintech lending applications, identify which Fintech Lending is licensed and which Fintech lending is not licensed, and submit proposals to the Village Government, Regency Government and Fintech lending Companies, 2.) The easiest Fintech lending and financial institutions fastest in providing loans, so according to the author Fintech lending is the most suitable financial institution.